2017
DOI: 10.3389/fncel.2017.00116
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4-Mediated Glutamate-Induced Astrocyte Swelling Is Partially Mediated through Metabotropic Glutamate Receptor 5 Activation

Abstract: Astrocytes are one of the most abundant cell types in the mammalian central nervous system (CNS), and astrocyte swelling is the primary event associated with brain edema. Glutamate, the principal excitatory amino acid neurotransmitter in the CNS, is released at high levels after brain injury including cerebral ischemia. This leads to astrocyte swelling, which we previously demonstrated is related to metabotropic glutamate receptor (mGluR) activation. Aquaporin 4 (AQP4), the predominant water channel in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 66 publications
2
35
0
1
Order By: Relevance
“…In this study, we observed that astrocytes treated with α‐synuclein exhibited a significant decrease in cell survival, the latter response was strongly prevented by the blockade of Cx43 hemichannels rather than Panx1 channels. Relevantly, a recent study demonstrated that AQP4 water channel is crucial for the glutamate‐induced astrocyte swelling caused by mGluR 5 activation (Shi et al, ). Consistent with this, we observed that α‐synuclein‐evoked astrocyte death was strongly prevented by the blockade of both AQP4 or mGluR 5 , whereas inhibition of NDMA receptors resulted in similar weak protection than Panx1 channel blockers.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, we observed that astrocytes treated with α‐synuclein exhibited a significant decrease in cell survival, the latter response was strongly prevented by the blockade of Cx43 hemichannels rather than Panx1 channels. Relevantly, a recent study demonstrated that AQP4 water channel is crucial for the glutamate‐induced astrocyte swelling caused by mGluR 5 activation (Shi et al, ). Consistent with this, we observed that α‐synuclein‐evoked astrocyte death was strongly prevented by the blockade of both AQP4 or mGluR 5 , whereas inhibition of NDMA receptors resulted in similar weak protection than Panx1 channel blockers.…”
Section: Discussionmentioning
confidence: 96%
“…Cerebral oedema is a potentially lethal pathological state that occurs after brain injury, and it is also one of the most serious consequences of acute CO poisoning. Cerebral oedema is featured by accumulation of water molecules in brain cells and or in the extracellular space, which can be mainly classified into interstitial cerebral oedema, osmotic cerebral oedema, cytotoxic cerebral oedema and vasogenic cerebral oedema . Comprehensive molecular mechanisms in the acute CO poisoning remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate excitotoxicity, as noted above, is one of the major causes of ischemic injury, and glutamate transporters on oligodendrocytes, astrocytes, and microglia that under normal conditions mediate uptake of extracellular glutamate to maintain low levels in the extracellular space, in ischemia release glutamate into the extracellular space (Mifsud et al, 2014). Furthermore, brain injury-induced astrocyte swelling is likely mediated by glutamate transporters and metabotropic glutamate receptors (Shi et al, 2017), and it is well known that oligodendrocytes are susceptible to excitotoxicity mediated by AMPA/kainate ionotropic glutamate receptors (Mifsud et al, 2014). There is significant developmental upregulation of these non-NMDA receptors, and it has recently been shown that selective upregulation and downregulation of specific subunits of the NMDA receptors in subjects with periventricular leukomalacia may underlie NMDA-mediated vulnerability in the developing brain (Jantzie et al, 2015; Mifsud et al, 2014).…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…Astrocyte functions in the ‘healthy’ CNS include uptake of potassium, water (astrocytes contain abundant aquaporin-4, a water channel; Moftakhar et al, 2010; Shi et al, 2017), and neurotransmitters (glutamate, GABA, glycine), and release of energy substrates (e.g. lactate), neurotransmitter precursors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation